Repellent Effect of Homemade Vaporizer on Aedes aegypti (Diptera: Culicidae); using Essential Oil of Tagetes erecta (Asteraceae) Flowers - K.M.D.D. Weerasekara; H.M.N. Sandamali; G.A.J.S.K. Jayasooriya (Advances in Technology, 2026)
Aedes aegypti (Diptera: Culicidae) mosquito, a major vector for dengue fever, poses a significant public health issue in Sri Lanka. Synthetic repellents are commonly used; concerns over their safety and environmental impact highlight the need for effective natural alternatives. This study evaluates the effectiveness of essential oil derived from African marigold (Tagetes erecta) flowers as a natural mosquito repellent, presenting an eco- friendly alternative to synthetic repellents. The essential oil was extracted using steam distillation. Approximately 100 g of air-dried marigold flowers were used per extraction, yielding about 0.25 mL of oil per 100 g of flowers. The repellent efficacy was assessed following World Health Organization guidelines, using one control cage and three treatment cages [size (30×30×30) cm3 , temperature 28 ± 3 °C, and a humidity of 80 ± 5%] each containing 50 Aedes aegypti mosquitoes. Six different concentrations of the essential oil diluted with ethanol (5, 6, 7, 8, 9, and 10%) vw̌ere applied to a 600 cm² area on the forearms of a single volunteer, restricting the mosquitoes’ landing area to the hands. Each concentration was tested in triplicate, with a 30- minute interval between applications to maintain consistency. Mosquito landings were counted, and percent repellence was calculated as a proportion of the number of mosquito landings on the treated arm to the number of landings on the control arm of the same individual. Probit values of repellence were plotted against log doses. Statistical validation of the equation was tested through linear regression analysis. The essential oil of Tagetes erecta demonstrated high repellent efficacy in both laboratory and field settings, with ED₅₀ and ED₉₉.₉ values of 5.98 ± 0.92% and 9.64 ± 1.63%, respectively, and provided complete protection for up to 150 ± 10 minutes under controlled conditions. Field application using a homemade vaporizer containing the essential oil (25 mL) extended protection up to 180 minutes, confirming the effectiveness of African marigold essential oil as a natural, eco- friendly repellent against dengue vector mosquitoes.